Unmasking Bladder Cancer: A Case of Macrohematuria during Rivaroxaban Therapy - Suha Al Fathima Mohamed Al Sabry; Gamage Ravindi Lakma Perera; Balapuwaduge Shayami Michelle Mendis; Karpovich Yulia Ivanovna; Karpovich Yuri Leonidovich (Medical Science: Trends and Innovations Vol. 7, 2025)
Background: Bladder cancer is the tenth most common cancer worldwide and the most common cancer of the urinary tract. Rivaroxaban is a directly acting, oral anti-coagulant (factor Xa inhibitor) that is used to treat and prevent the formation of blood clots. A common side effect of this drug is an increase in bleeding tendencies, which can potentially lead to macroscopic hematuria. However, it is important to note that macroscopic hematuria can appear in several other conditions including urological malignancies. Objective: This report outlines the case of a patient on long term rivaroxaban therapy who developed macroscopic hematuria, not as a consequence of the medication but rather due to bladder cancer. The Case: This study reports a case of a 69-year-old male patient with a history of myocardial infarction undergoing long term Rivaroxaban therapy, presenting with macroscopic hematuria and frequent urination. The clinical history and presenting symptoms were consistent with the side effects of prolonged use of Rivaroxaban, but further investigations revealed the presence of a tumor in the bladder which was instead found to be the cause of macroscopic hematuria. Conclusion: Although macroscopic hematuria is a very common side effect of Rivaroxaban therapy, it is vital to consider other conditions that can present with the same symptoms. This case shows the need for healthcare practitioners to be more vigilant when handling patients with anti-coagulant induced hematuria and the importance of thoroughly examining every patient before coming to a conclusive diagnosis.